Analyzing the Drivers of the Shadow Economy for the Case of the CESEE Region - Amir, Aysel; Gokmenoglu, Korhan (Ekonomický časopis/Journal of Economics, 2025)
This study explores the influence of financial development on the shadow economy, alongside other possible determinants, for the CESEE region. To this objective, we used a panel dataset of annual figures for eleven CESEE countries from 2003 to 2019. To estimate the long-run coefficients, panel FMOLS and DOLS were employed. Our findings suggest that an increase in financial development and tax burden leads to the enlargement of the shadow economy. While improvements in institutional quality, trade openness, and economic freedom reduce the magnitude of the shadow economy. The study’s results offer various policy recommendations that can be used to combat the shadow economy in CESEE countries. Tax policy and institutional reforms are encouraged to promote greater trust within institutions, enabling the shift of economic activities from the shadow to the formal economy.